Genetic testing and sports medicine ethics - McNamee, M. J.; Müller, A.; van Hilvoorde, I.; Holm, S. (Sports Medicine, 2009)
Sports medicine ethics is neither a well established branch of sports medicine nor of medical ethics. It is therefore important to raise to more general awareness some of the significant ethical implications of sports medicine practices. The field of genetics in sports is likewise in its infancy and raises significant ethical concerns. It is not yet clear how genetics will alter our understanding of human potential and performance in sports. While a number of professional medical bodies accept genetic interventions of a therapeutic nature, we argue that the use of genetic technologies to predict sports potential may well breach both the European bioethics convention and North American anti-discrimination legislation, which are designed to support important ethical ideals and the ongoing commitment of the physician to the welfare of their patient. We highlight further ethical problems associated with confidentiality and consent that may arise in genetic testing as opposed to more conventional methods of testing in sports medicine. We conclude that genetic testing in sport that is not strictly limited to the protection of the athlete against harm, should be viewed in a very sceptical light by sports medicine professionals.